2015
DOI: 10.1016/j.mgene.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase gene C677T polymorphism and breast cancer risk: Evidence for genetic susceptibility

Abstract: There are several evidences supporting the role of 5–10 methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms in breast cancer (BC). Case control association studies on breast cancer have been repeatedly performed over the last two decades, but results are inconsistent. We performed a meta-analysis to confirm the association between MTHFR C677T polymorphism and BC risk.The articles were retrieved by searching the PubMed, Google Scholar, and Springer Link databases. Crude odds ratios (OR) with 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 113 publications
1
32
0
Order By: Relevance
“…The results of our meta-analysis corroborated with other meta-analyses (Yu and Chen 2012;Liang et al 2013;Castro-Quezada et al 2014); (Li et al 2014a;Rai 2014;Pooja et al 2015;Kumar et al 2015) in showing MTHFR C677T as a risk factor for breast cancer. The null association of MTR A2756G in random effects model and an inverse association with breast cancer in Caucasians were consistent with the meta-analysis of Zhong et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…The results of our meta-analysis corroborated with other meta-analyses (Yu and Chen 2012;Liang et al 2013;Castro-Quezada et al 2014); (Li et al 2014a;Rai 2014;Pooja et al 2015;Kumar et al 2015) in showing MTHFR C677T as a risk factor for breast cancer. The null association of MTR A2756G in random effects model and an inverse association with breast cancer in Caucasians were consistent with the meta-analysis of Zhong et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…A decreased methylation pattern may cause uncontrolled gene expression and genomic instability, and induce carcinogenesis [19,20]. To date, a lot of studies have reported on the association between the MTHFR gene C677T polymorphism and breast cancer; however, results have remained controversial [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, 2 large meta-analyses about the MTHFR gene C677T polymorphism and breast cancer were published [21,22]. The first analyzed 41 studies; 4 of these were from Turkey and included 16,480 breast cancer patients and 22,388 controls [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter meta-analysis suggested the risk of breast cancer was significantly associated with postmenopausal status (48). Also, 3 recent meta-analyses suggested a significant relation between MTHFR 677TT genotype and breast cancer risk in Asian populations (49)(50)(51). The association of MTHFR C677T polymorphism with hypomethylation of DNA might suggest a role for this polymorphism in development of cancer.…”
Section: Mthfr C677t Variants In Breast Cancermentioning
confidence: 93%